Dual-Feed Small-Size Penta-Band PIFA for LTE/WWAN Mobile Handset Applications - Mingyang Liu; Bin Zhao (International Journal of Antennas and Propagation)
A dual-feed small-size penta-band PIFA for LTE/WWAN mobile handset applications is presented. The proposed PIFA is composed of a simple U-shaped patch with dual-shorting pins connected to the ground plane. The patch, having a low profile of 5 mm, has dimensions of about 10 × 35 mm2. The antenna is excited at one arm of the U-shaped radiating patch to cover the higher band of GSM1800/1900/UMTS2100/LTE2300/2500, while it is excited at the other arm to realize the GSM900. In this way, the proposed PIFA achieves enhanced bandwidth coverage with no increased dimensions and additional active switches. In addition, the matching networks, employed on both feeds, ensure a high electrical insulation between the low and the high frequency bands, covered by the antenna. The measured antenna efficiency is 45%~50% and over 60% for the lower band and the higher band, respectively. A prototype of the proposed PIFA with dual-feed and dual-shorting pins was fabricated. The measured results including reflection coefficients and radiation characteristics are presented.